Pedagogic competence of teachers in religious moderation-based islamic education for disabled students - Mindani Mindani; Hengki Satrisno; Nova Asvio (JPPI (Jurnal Penelitian Pendidikan Indonesia), 2022)
This study explored: 1) the understanding and skills of teachers in managing PAI learning based on religious moderation for people with disabilities; 2) the form of religious moderation in the teaching of PAI based on religious moderation for people with disabilities; and 3) factors that influence the teaching of religious moderation in religious moderation-based PAI teaching for people with disabilities. Descriptive qualitative field research method was used in this study. The results of the study revealed that: 1) The ability of teachers in carrying out learning was quite good; 2) The forms of religious moderation that are accustomed to the extraordinary schools of Bengkulu city, including attitudes of tolerance, tolerance, egalitarian (equality), caring (empathy), compassion and mutual help or mutual assistance, and responsibility; and 3) Factors that influence the implementation of Islamic religious education learning activities based on religious moderation for the disabled at special schools in Bengkulu city, including supporting factors (stakeholder commitment, facilities and infrastructure, rules and curriculum) and inhibiting factors (knowledge, parental commitment), and teacher commitment).